Ethno-political Processes in V-VIII Centuries in Uzbekistan - Nosirjon, Buvakov (International Journal of Psychosocial Rehabilitation, 2020)
This article analyzes the ethnopolitical processes that took place in the V-VIII centuries on the territory of Uzbekistan. It is known that in the periods under study, it is impossible to limit oneself only to the territory of Uzbekistan. For this reason, the author focuses mainly on ethno-political processes in Central Asia. In particular, some processes in the decline of the Kushan and Kangh states, the Huns, the Kidarites, and the Khionites (Chionites) were analyzed, mainly focused on the ethno-political processes in the Turkish khanate. According to the author, this period is still a vital subject for research. Because there are great shortcomings in the sources and literature of this period.